Considering the work in workplace bullying : a sociological approach - Calvert, Emma (Trinity College (Dublin, Ireland). Department of Sociology, 2011)
In recent years, bullying has come to be established as a significant issue for contemporary workplaces, in Ireland as elsewhere. Our research knowledge is largely psychologically-based, with many studies focusing on the personality characteristics of the victim or perpetrator and bullying has been viewed as an "interpersonal" conflict. However, when other characteristics are considered, research has repeatedly found that workers in the public sector are more likely to report bullying than private sector. In order to investigate this finding, the current study takes a sociological approach and focuses on the workplace, which is arguably shaped by its broader institutional context in terms of the labour market, with specific sectoral characteristics. Part of the rising concerns about workplace bullying can be contextualised in ternis of the increasing emphasis placed on the psychological well-being of workers, with the recognition of "new risks" of stress and harassment. However, this focus on individual subjective well-being arguably obscures the collective nature of the phenomena, in terms of its association with the "changing workplace".
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin